Chromosome-level genome assembly of stem borer Batocera rufomaculata using PacBio HiFi and Hi-C sequencing - Jinwu He; Tianqi Bai; Wenting Wan; Zhiwei Dong; Yangjie Wang; Hongrui Zhang; Xueyan Li (Scientific Data)
Abstract Batocera rufomaculata (Cerambycidae: Lamiinae), a prominent representative of longhorned beetles, is a globally significant stem-boring pest, infesting over 50 species of deciduous trees. Despite its substantial ecological and economic impact, the genomic basis underlying its host adaptation remain poorly understood. Here, we present a chromosome-level genome assembly of B. rufomaculata, constructed using a combination of Illumina, PacBio HiFi, and Hi-C sequencing data. The genome spans 338.08 Mb, with a scaffold N50 of 37.00 Mb, and is organized into 10 pseudo-chromosomes, including a chromosome X validated by genome collinearity and sequencing depth analyses. Repetitive elements constitute 27.89% of the genome, totaling 94.29 Mb. Out of 17,887 predicted genes, 12,729 were functionally annotated with at least one supporting evidence. The high-quality genome assembly and annotation were confirmed by multiple metrics, including genome size, reads mapping rate (>99.5%), BUSCO completeness (>97.1%), and collinearity analyses. This comprehensive genomic resource provides a foundation for investigating the ecological adaptation of B. rufomaculata and offers valuable insights into the genetic mechanisms that could inform pest management strategies.